Analisis Kinerja Pengelolaan Keuangan Daerah Kota Tanjung Pinang - Sapitri, Nor; Pangestoeti, Wahjoe; Putri, Dea Pratama; Akbar, Muhammad Rizky (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Analysis of the performance of local government financial management in the city of Tanjungpinang is a research that aims to evaluate the efficiency and effectiveness of local government financial management in the city of Tanjunpinang. This study includes analysis of various aspects such as income, expenditure, investment and regional debt management. The aim is to find out improvement plans to improve the quality of public financial management in the city of Tanjungpinang by analyzing regional financial performance in detail. The financial management performance of the city of Tanjung Pinang is measured using the method